Mapping cover-thickness to UNCOVER basement and deep Earth architecture and processes. Issue 1 (1st December 2016) - Czarnota, Karol; Meixner, Tony; Wilford, John; Gorbatov, Alexei
Abstract : Under the UNCOVER initiative it is generally accepted that construction of accurate cover-thickness maps is the most tractable and urgent means of facilitating resource exploration under cover. To meet this goal we have been undertaking benchmarking of various geophysical techniques, constructing a national database of Estimates of Geological and Geophysical Surfaces (EGGS) to store legacy estimates and developing machine learning algorithms to interpolate between these estimates. Benchmarking magnetic top estimates to ~700 drill sites across the Murray Basin highlights the importance of performing estimates using profile data as opposed to grids. Inversion of horizontal to vertical spectral ratio data, derived from single broadband seismometers, reveals surprisingly robust cover-thickness estimates. While these insights are directly relevant in supporting drilling programs they can also be used to constrain deep Earth architecture and processes. We show that inversion of basin subsidence data can be used to constrain lithospheric thickness and mapped chrono-stratigraphic surfaces can be used to test models of uplift of the Australian continent related to convective flow within the Earth's mantle.